2013
DOI: 10.1016/j.bbadis.2013.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Combination of lipid metabolism alterations and their sensitivity to inflammatory cytokines in human lipin-1-deficient myoblasts

Abstract: Lipin-1 deficiency is associated with massive rhabdomyolysis episodes in humans, precipitated by febrile illnesses. Despite well-known roles of lipin-1 in lipid biosynthesis and transcriptional regulation, the pathogenic mechanisms leading to rhabdomyolysis remain unknown. Here we show that primary myoblasts from lipin-1-deficient patients exhibit a dramatic decrease in LPIN1 expression and phosphatidic acid phosphatase 1 activity, and a significant accumulation of lipid droplets (LD). The expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 60 publications
4
61
0
1
Order By: Relevance
“…Previous work showed that PAP activity was markedly reduced in isolated myocytes from three patients with lipin 1 mutations, including the E766-S838_del mutation studied herein (Michot et al 2013). However, those cells exhibited a complete loss of lipin 1 mRNA expression, and a distinction regarding impaired transcriptional regulatory function or PAP activity could not be made.…”
Section: Discussionmentioning
confidence: 64%
“…Previous work showed that PAP activity was markedly reduced in isolated myocytes from three patients with lipin 1 mutations, including the E766-S838_del mutation studied herein (Michot et al 2013). However, those cells exhibited a complete loss of lipin 1 mRNA expression, and a distinction regarding impaired transcriptional regulatory function or PAP activity could not be made.…”
Section: Discussionmentioning
confidence: 64%
“…These phenotypic changes in lipid metabolism are directly or indirectly coupled to other phenotypes, such as an irregular expansion of the nuclear/ER membrane, marked vacuole fragmentation, and increased fatty acid-induced lipotoxicity (11,29,34,35,38). Similarly, in mammalian cells, loss of lipin PAP activity results in metabolic disorders that include lipodystrophy, insulin resistance, peripheral neuropathy, rhabdomyolysis, and inflammation (30,(93)(94)(95)(96)(97)(98)(99)(100)(101).…”
Section: Discussionmentioning
confidence: 99%
“…1A) (10,14). The losses of or defects in mammalian lipin PAP enzymes underlie metabolic disorders that include lipodystrophy and insulin resistance, peripheral neuropathy, myoglobinuria, and inflammation (7,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Together, these observations highlight the importance of PAP in lipid metabolism and cell physiology and the need to understand the genetic and biochemical regulations of the enzyme.…”
mentioning
confidence: 97%